Co‐occurrence of papillomas related to Equus caballus papillomavirus type 2 and cutaneous habronemiasis. (4th April 2021) - Vichi, G.; Porcellato, I.; Mechelli, L.; Fantauzzo, G.; Razzuoli, E.; Modesto, P.; Mecocci, S.; Brachelente, C.
Summary: The present report describes a case of cutaneous papillomatosis related to equine papillomavirus type 2 (EcPV2) with concomitant cutaneous habronemiasis. A 2‐year‐old female Pura Raza Española horse was referred for a dermatological evaluation because of the onset of cutaneous multifocal, nodular lesions on the face characterised by a warty and partially ulcerated overlying epidermis. Multiple biopsies were taken from these lesions, and cutaneous viral papillomas with a concomitant severe focal eosinophilic dermatitis with intralesional Habronematidae nematode larvae were diagnosed. Immunohistochemistry revealed papillomaviral capsid protein L1 in the epidermal proliferative lesion, confirming the presence of a productive infection. Rt‐qPCR confirmed the presence of EcPV type 2. To the authors' knowledge, this is the first report of EcPV2‐related papillomas with concurrent habronemiasis.